Pengaruh Biaya Promosi Terhadap Penjualan Pada Toko Rilexindo Auto Accessories - Ria Saryati; Wella Sandria; Sesraria Yuvanda (J-MAS (Jurnal Manajemen dan Sains), 2020)
This research aims to find out how sales are growing in Rilexindo Auto Accessories stores and how promotional costs affect sales in Riexindo Auto Accessories stores. The research was conducted in one of the branches of rilexindo group company namely 'Rilexindo Auto Accessories' store using sales data and promotional costs from 2017 - 2019 which is divided into 4 quarters. The data is processed with a development formula and a simple regression method with the promotional cost as a free variable (X) with sales as a bound variable (Y). The results showed that sales growth at the 'Rilexindo Auto Accessories' store with the highest sales was in 2017 in the 2nd quarter of Rp. 1,227,010,000, and the lowest sales were in the 3rd quarter of 2019 at Rp. 415,800,000. Promotional costs significantly affect sales at Rilexindo Auto Accessories stores, this is indicated by thitung > ttabel's 21,482 > 2.26 with a correlation coefficient of 0.990 and a significance rate of 0.000 (<0.05).